Synthetic, mechanistic and biological studies of novel metal-imidazo[1,2-a]pyridines and xanthones - Dam, Jean (My University, 2016)
The work detailed in this PhD involves two distinct, separate areas of research. The first project involved an investigation into the synthesis, characterisation and metal-chelation of pyrido-imidazo[1,2-a]pyridines in the search for new compounds for the treatment of cancer. Previously in our laboratories at the University of the Witwatersrand a small library of imidazo[1,2-a]pyridines were synthesized that showed significant activity (IC50 values between 6.57-21.98 μM) against Caco-2 and HT-29 colorectal cancer cell lines while showing little cytotoxicity towards white blood cells; significantly less than camptothecin the ‘golden standard’. In an attempt to improve the overall activity of the imidazo[1,2-a]pyridines methodology was developed to coordinate zinc, copper and platinum to the imidazo[1,2-a]pyridines to generate novel metal-imidazo[1,2-a]pyridine complexes. These novel compounds were characterised by NMR spectroscopy (where possible) and Single Crystal X-ray Diffraction (SCXRD) and tested against colorectal (Caco-2 and HT-29), leukemic (K562 and HL-60) and breast (MCF-7 and MDA-MB231) cancer cell lines, where the copper-containing compounds showed the most significant activity. A library of 11 copper complexes screened showed excellent activity in all the cell lines tested, some of which were more active than camptothecin. The second part of this PhD involved a detailed investigation into novel methodology to synthesize xanthones and related diones, for example such as 4a-methoxy-2H-xanthene-2,9(4aH)-dione, discovered in our laboratory. Initially this reaction was reported to be mediated by ceric ammonium nitrate (CAN), however it was determined during the course of this investigation that the novel reaction was actually mediated by ceric ammonium sulfate (CAS) and that different products were isolated depending on which reagent (CAN or CAS) was used. In this thesis, the mechanism of the reaction was probed and it was determined that the electronic nature of the starting benzophenone (e.g. (2-hydroxyphenyl)(2,4,6-trimethoxyphenyl)methanone) plays a crucial role in the outcome of the reaction. In addition to the furnishing of xanthones (e.g. 4-methoxy-9H-xanthen-9-one) and spirofurans (such as 2',6'-dimethoxy-3H-spiro[benzofuran-2,1'-cyclohexa[2,5]diene]-3,4'-dione) using this CAS-mediated reaction, novel biaryl-fused dimers (e.g. (4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diyl)bis((2,4-dimethoxyphenyl)methanone)) were also isolated and these results were explained by the mechanisms detailed in this work. Reliable methodology was developed using a sodium dithionite-mediated method for the conversion of dione products (such as 4a-methoxy-2H-xanthene-2,9(4aH)-dione) to hydroxy-containing xanthones (such as 7-hydroxy-9H-xanthen-9-one). iv Finally, as a proof of concept, this novel CAS-mediated methodology was extended to the synthesis of the nitrogen-containing derivatives, the acridones, and a single acridone, 10-benzyl-2-methoxyacridin-9(10H)-one, was successfully synthesized using CAS as the reagent, albeit in a low yield.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy Submitted June 2016.
Keywords: Cancer, Treatment; Imidazopyridines; Xanthone